New insights into tuberous sclerosis complex: from structure to pathogenesis - Chen, Chao-Sheng; Aylett, Christopher H. S. (Frontiers in Cell and Developmental Biology, 2025)
Tuberous sclerosis complex is a genetic disorder characterised by the formation of benign tumours in multiple organs, primarily due to pathogenic variants in the TSC1 and TSC2 tumour suppressor genes. These genes encode hamartin and tuberin, respectively, which together with TBC1D7 form a crucial protein complex regulating cell growth and proliferation through mTOR signalling and other pathways. This review provides an overview of recent progress in understanding the molecular structure and function of this key protein complex, its role in cellular processes, pathogenesis, and current and future therapeutic strategies.